Detection and Antimicrobial Resistance of Staphylococcus Species from Chicken, Chicken Litter, and Humans in Addis Ababa, Ethiopia - Fufa Abunna; Biyansa Adugna; Takele Beyene Tufa; Dinka Ayana; Fanta D. Gutema; Hika Waktole; Fikru Regassa; Reta D. Abdi (Veterinary Medicine International)
Background. In veterinary medicine, three Staphylococcus species are of particular importance as primary causes of specific diseases; S. aureus (mastitis in ruminants, equine botryomycosis, and bumble foot in poultry), S. hycus (porcine exudative epidermitis), and S. intermedius (canine pyoderma). The disease conditions caused by Staphylococcus in poultry vary with site, route, and predisposing factors include wounds as a result of fighting/cannibalism, immunosuppression based on virus infection or parasite infestation, and bad husbandry conditions (overcrowding). The objectives of this study were to isolate and identify Staphylococcus spp from chicken and chicken litter and personnel at chicken farm and to determine the antimicrobial susceptibility profile of the isolates. Methods. A cross-sectional study was conducted on apparently healthy chickens, farm personnel, and chicken litter at poultry farms in Addis Ababa, Ethiopia. A total of 222 samples consisting of 101 cloacal swabs, 90 tracheal swabs, 17 pooled litter swabs, 7 nasal swabs, and 7 pooled hand and boot swabs were collected from six farms and examined for the presence of Staphylococcus species. Antimicrobial resistance against 10 antimicrobial agents was also conducted following recommended standard procedures. Results. Overall proportion of Staphylococcus was 64/222 (28.83%). Of the isolates, 40/64 (62.5%), 11/64 (17.2%), 3/64 (4.7%), and 10/64 (15.6%), were S. aureus, S. hycus, S. intermedius, and coagulase-negative staphylococci (CNS), respectively. Only one isolate of S. aureus was susceptible to all antimicrobials tested. Of the 10 antibiotics tested, the isolates demonstrated highest resistance against Penicillin G (96.9%) followed by Tetracycline (78.1%), and Amoxicillin and Erythromycin at the same level (65.6%). Conversely, the isolates were highly susceptible to Ciprofloxacin (95.3%) followed by Sulphamethoxazole-trimethoprim (85.9%). Out of 64 isolates, 61/64 (95.3%) were resistant to three or more antimicrobials tested. Of the isolates, 38/40 (95%) S. aureus, 10/11 (90.9%) S. hycus, 3/3 (100%) S. intermedius, and 10/10 (100%) CNS showed multidrug resistance. Conclusion. This study showed a considerable proportion of Staphylococcus spp in chicken litter and farm workers with a potential source of resistant Staphylococcus species, and more importantly multidrug resistance strains. Further studies on molecular characterization of the isolates will be essential to identify the resistant genes and establish epidemiological links in the transmission dynamics of resistant Staphylococcus species between poultry and humans.